(3LGhjOGf NQOs - (3CMeO Hf eMeO Hf jYbhH perSncnhrjg, CHh Ydj,J (B421 (3g` s ((3eSYhO Hf ehOhO Hf Rfcj Hf BbSfbQ s)
(3ChdgG (B:s
(3bGd CMeO Hf eMeO Hf jYbhH eSchjg(B: (3HYO MeO Gddg hGdKfGA Ydjg HeG gh Cgdg Efj cfJ bQCJ aj GdMOGKI cJGHG dCHj YKeGf GdLGMX jYQa HGSJWGdI Gdage jPcQ ajg cJGHG jYQa HLGhjOGf NQO s
(3BNQgG (B:s
(3CYfj LGhjOGf NQO adPdc jLH Cf JbJUQ Ydi eHdZ eG CMUjKJg hdG JWdH GdZGjI ajeG dG ZGjI dg hGdSdGe jdjg OYhGJ eSJLGHg hdZR bGHS hJaSjQ GHf bdS GdSbQGWj GdCadGWhfj dg s
(3GdfSNI HgG MhGTs
(3fSNI NRGFfjI fajSIs
(3HgG bQGAGJ hJedcGJs
(3hJYdjbGJ s
(3fbdg ef GddSGf GdbOje Edi GddSGf GdaGQSj cfLhQ Hf GSafOjGQ, hRjQ edc EjQGf TgQ, hJQLeg ddYQHjI GdMSf Hf Sgd hSeGg JUajI GdCPgGf hfaGP GdacQ hTMP GdbdhH , hJeeg GdeDda hLGA Hg cebOeI dcJGHI BOGH GdYQH hGd s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs